THE EFFECT OF DIGITAL CLASS IMPLEMENTATION ON COGNITIVE ABILITY AND SELF-REGULATED LEARNING - Rafiah Wardani Daulay; Ely Djulia; Supraba Ika Sari (Jurnal Pelita Pendidikan, 2022)
This study aims to determine the effect of the implementation of the Learning House Digital Portal Class on cognitive abilities and self-regulated learning of students in Evolution material in class XII IPA SMA Negeri 11 Medan. This type of research is a quasi-experimental type of research. The research sample was taken by purposive sampling. The sample consisted of 2 classes, namely class XII IPA 6 and class XII IPA 5. The instruments used to collect data were tests of students' cognitive abilities in the form of multiple choice and self-regulated learning questionnaires. The results showed that the average value of students' cognitive abilities using the Digital Class was 83.87 ± 11.72, which was better than the cognitive abilities of students who did not use the Digital Class, with an average of 77.33 ± 10.57. Analysis of hypothesis testing using SPSS21 with the independent t-test method and a confidence level of α = 0.05 shows the significance value on the average value of cognitive ability and the average value of self-regulated learning does not differ significantly which means that in this study H0 is rejected whereas Ha is accepted. Thus it can be concluded that there is an influence on the cognitive abilities and self-regulated learning of students implemented by the Digital Home Learning Portal Class on evolution material in class XII IPA SMA Negeri 11 Medan.